Plumage evolution in Neotropical finches: An evolutionary and behavioral approach (2021)
In this dissertation, I addressed evolutionary and behavioral hypotheses related with the ecological and social mechanisms underlying the origin of plumage traits and geographic variation in Neotropical birds. The protagonists of this story are finches in the genus Arremon, a diverse group of lowland and highland birds ranging from northern Mexico to southern Argentina, whose geographic variation in plumage patches and evolutionary history has called the attention of taxonomists and evolutionary biologists for almost a century. My approach involved museum and lab work, as well as detailed observations of behavior in the field. I used these data integrating several analytical approaches like phylogenetic comparative methods, design and implementation of behavioral experiments, combined with analyses of physiological and ecological attributes of free-living individuals. Conducting my research program required building a novel natural history baseline and a robust phylogenetic framework, for which I collaborated with colleagues and students I supervised. Manuscripts resulting from such work are included as appendices, with the core of my dissertation corresponding to three original chapters. In the first chapter, I studied the association between environment and the evolution of plumages traits across the genus Arremon. I used a multilocus molecular phylogeny of the genus to expand previous analyses on trait evolution focused on a single species complex to the whole genus and, for the first time, examined links between phenotypes and environments. In the second chapter, I studied whether novel plumage traits may provide a competitive advantage (or disadvantage) relative to local traits during male-male contests, and therefore may represent a mechanism driving population divergence. In the third chapter, I studied potential social and physiological costs associated to signaling a novel trait.